2020
DOI: 10.3847/1538-4357/abb5a7
|View full text |Cite
|
Sign up to set email alerts
|

Solar Wind Turbulence Around Mars: Relation between the Energy Cascade Rate and the Proton Cyclotron Waves Activity

Abstract: • We estimate, for the first time, the incompressible energy cascade rate obtained in the solar wind near Mars. • We find that the nonlinear cascade of energy is slightly amplified when proton cyclotron waves are present in the plasma. • These statistical results show the presence of Alfvénic and non Alfvénic turbulent fluctuations in a magnetic dominant regime.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 92 publications
2
35
1
Order By: Relevance
“…Additionally, they found that a fully developed energy cascade is absent in the magnetosheath of Mars, but present in the magnetic pileup boundary (also known as the induced magnetosphere boundary; see Espley, 2018 for a debate on the nomenclature). A study conducted by Andrés et al (2020) estimated the incompressible energy cascade rate at MHD scales in the plasma upstream of the bow shock for events with and without proton cyclotron wave activity. To date, there have been no known studies that examine the proton temperature anisotropy at Mars.…”
Section: The Martian Plasma Environmentmentioning
confidence: 99%
“…Additionally, they found that a fully developed energy cascade is absent in the magnetosheath of Mars, but present in the magnetic pileup boundary (also known as the induced magnetosphere boundary; see Espley, 2018 for a debate on the nomenclature). A study conducted by Andrés et al (2020) estimated the incompressible energy cascade rate at MHD scales in the plasma upstream of the bow shock for events with and without proton cyclotron wave activity. To date, there have been no known studies that examine the proton temperature anisotropy at Mars.…”
Section: The Martian Plasma Environmentmentioning
confidence: 99%
“…In addition, MGS did not possess an onboard SW ion detection instrument to study SW properties during PCW events. As MAVEN provides both magnetic field and SW measurements, this mission presents an excellent opportunity to perform studies focused on these low frequency plasma waves (e.g., Andrés et al, 2020;Halekas et al, 2020;Liu et al, 2020…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the importance of the magnetohydrodynamic (MHD) turbulence for the understanding the energy transfer between Sun and planetary magnetospheres (Bolzan and Echer, 2014;Echer and Bolzan, 2016;Banerjee et al, 2016;Andrés et al, 2020). Echer and Bolzan (2014), analyzing data from Uranus' foreshock turbulence, shown that intermittent waves can play important contribution to energy of foreshock waves.…”
Section: Introductionmentioning
confidence: 99%
“…Echer and Bolzan (2014), analyzing data from Uranus' foreshock turbulence, shown that intermittent waves can play important contribution to energy of foreshock waves. Andrés et al (2020) have computed the energy cascade in the Martian upstream region using MAVEN data. Those authors have observed that the nonlinear cascade at the MHD scales shows a slight amplification for intervals with proton cyclotron wave activity around the perihelion.…”
Section: Introductionmentioning
confidence: 99%